AB0557 Behçet's Disease in Women: A Tunisian Series of 135 Patients. (15th July 2016) - Ben Salem, T.; Tougorti, M.; Naceur, I.; Ben Ghorbel, I.; Lamloum, M.; Houman, M.H.
Abstract : Objectives: The aim of this study was to describe clinical and genetic characteristics of Behçet's disease (BD) in women and to compare them with those in men. Methods: 430 cases of patients with BD (fulfilling criteria of the International Study Group for BD) were studied. Clinical and genetic characteristics of women with BD were noted, than compared to those observed in male BD patients. Data were compared using the Chi2 test and the Fisher exact test. Results: 135 women were studied; the mean age at the onset of the BD was at 28.7 years. The average age at BD diagnosis was 34.64 years. Genital aphtosis was noted in 71.9% of patients and skin lesions in 83% (pseudofolliculitis: 63.7%, erythema nodosum: 28.9% and positive pathergy test: 56.6%). Ocular involvement in type of uveitis was noted in 43% of patients and retinal vasculitis in 23.7% of them. 65% of women complained of arthralgia while only 7.4% of them presented arthritis. Neurological manifestations were objectified in 31.9% of patients. Deep vein thrombosis (DVT) and arterial disease were noted respectively in 15.6% and 0.7% of cases. HLA B51 was present in 47.7% of women with BD in our series. Compared to male patients, women had significantly less genital aphtosis (71.9% vs 83%, p=0.008), pseudofolliculitis (63.7% vs 79.6%, p<0.0001), DVT (15.6% vs 33.2%, p<0.0001) and arterial disease (0.7% vs 9.2%, p=0.001). On the contrary, arthralgia (65% vs 47.5%, p=0.007) and erythema nodosum (28.9% vs 11.6%, p<0.0001) were significantly more frequent in women. Conclusions: Our results were similar to other BD series regarding the high incidence of erythema nodosum and joint manifestations in women, and the lower frequencies of genital aphtosis and vascular involvements compared to men. Disclosure of Interest: None declared